Relevansi Konsepsi Rahmatan Lil Alamin dengan Keragaman Umat Beragama - Solikhun, Solikhun (Hanifiya: Jurnal Studi Agama-Agama, 2021)
The impression of western world to the eastern has not shown a positive proportion. It always considers the latter as a minor. It is more so after the incident of WTC 9 September 2001. The eastern or as an assertive known as a terrorist, unhuman, and far from humane proportion. While in Islam itself, there is rahmatan li al-‘alamin. These things make the researcher interested in examining deeper what it means to be a rahmatan li al-‘alamin in Koran as a source of that word. Apart from the phrase rahmatan li al-‘alamin, a rahmat word is not connected to the li al-‘alamin word (universe) in the Koran. What also precisely is the difference between grace (rahmat) and rahmatan li al-‘alamin. Indonesia is a plural nation. That is not only ethnic, language, and custom tradition, but also religion. How is the relationship between faith in diversity frame? Is there relevance of li al-‘alamin in the diversity frame of religious people? Some questions need to search for answer in various reverence. The nation's founders have been proud not to obtrude by doing sharia for the adherents is a space for tolerance and religious people.